Association between leisure-time physical activity and incident cancer risk: a nationwide population-based cohort study - Yun-Ju Lai; Chun-Chieh Wang; Yu-Kai Lin; Mei-Ju Chen; Yi-Sheng Chou; Chu-Chieh Chen; Chieh-Yu Liu; Shang-Jung Wu; Li-Fei Hsu; Jia-Hua Li; Yung-Feng Yen (SpringerOpen, 2024)
Abstract Background The effects of physical activity on the development of different types of cancers have not been comprehensively studied. This nationwide, population-based cohort study investigated the effects of leisure-time physical activity (LTPA) on the development of different types of cancer in Taiwanese adults. A total of 67,890 adult participants (≥ 18 y old) from five rounds (2001, 2005, 2009, 2013, and 2017) of the Taiwan National Health Interview Survey were included. LTPA was measured as the metabolic equivalent of task (MET) expenditure per week and was classified as inactive (< 1 MET-h), low (1-7.49 MET-h), or high (≥ 7.5 MET-h). The LTPA and other covariates were collected through in-person interviews at baseline. New-onset cancer was ascertained from histopathological reports. The Fine-Gray sub-distribution method, with death as a competing risk, was used to determine the impact of LTPA on incident cancer risk. Results During the 844,337 person-years of follow-up, 4,435 individuals developed cancer. Compared to inactive adults, individuals engaging in high levels of LTPA (≥ 7.5 MET-h/week) were significantly associated with a reduced risk of developing cancer (adjusted hazard ratio [aHR] = 0.93; 95% confidence interval [CI] = 0.87-0.99). However, those with low levels of LTPA (1-7.49 MET-h/week) did not exhibit a significant association with a reduced risk of developing cancer (aHR = 1.00; 95% CI = 0.92-1.10). When considering specific types of cancers, participants with high levels of LTPA (≥ 7.5 MET-h/week) had a significantly lower risk of developing bladder cancer (aHR = 0.68; 95% CI = 0.47-0.99), cervical cancer (aHR = 0.48; 95% CI = 0.24-0.95), and thyroid cancer (aHR = 0.64; 95% CI = 0.44-0.93). Conclusions Our findings suggest that high LTPA (≥ 7.5 MET-h/week) is significantly associated with a low risk of incident bladder, cervical, and thyroid cancers.